The Work of Authorship - van Eechoud, Mireille (Amsterdam University Press, 2014)
Technological and economic concerns have long been the drivers of debate about copyright. But diverse disciplines in the humanities - including literary studies, aesthetics, film studies, and the philosophy of art - have a great deal to offer if we wish to establish a more nuanced and useful conception of copyright and authorship. This volume brings together scholars from a range of disciplines to explore the challenges inherent in translating aesthetics and creativity studies to concepts of copyright, especially as longstanding approaches are troubled by the rise of the digital.